2010
DOI: 10.1111/j.1461-0248.2009.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asymmetric dispersal on the coexistence of competing species

Abstract: The global biodiversity crisis has made a priority of understanding biodiversity maintenance in ecological communities. It is increasingly apparent that dispersal patterns can have important effects on such maintenance processes. Nevertheless, most competition theory has focused on a small subset of the possible dispersal patterns in nature. Here, we show that spatially asymmetric dispersal, i.e. the disproportionate transport of propagules towards or away from particular habitat patches in a metacommunity, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
91
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 42 publications
10
91
1
Order By: Relevance
“…Mounting evidence suggests that species' dispersal patterns shape community and food web structure in many ecosystems [38][39][40][41][42] . For example, competing reef fish species in the Great Barrier Reef ecosystem appear to have different dispersal abilities, and this difference may explain the complex patterns of species coexistence observed across the Great Barrier Reef 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that species' dispersal patterns shape community and food web structure in many ecosystems [38][39][40][41][42] . For example, competing reef fish species in the Great Barrier Reef ecosystem appear to have different dispersal abilities, and this difference may explain the complex patterns of species coexistence observed across the Great Barrier Reef 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors include tidal patterns and oceanic currents (26)(27)(28) and the larvae's developing locomotive and sensory capabilities (23,(26)(27)(28). Dispersal is therefore highly variable, and both spatial (13,15) and temporal (9,11,28) variabilities interact to determine metacommunity dynamics and coexistence. In the second GBR example, we investigate whether species with different dispersal abilities can coexist in the presence of stochastic biophysical factors.…”
Section: Biophysical Dispersal Patternsmentioning
confidence: 99%
“…Interspecific dispersal differences can create ephemeral spatial niches in stochastic environments, and these are enough to allow species to coexist if their dispersal patterns are sufficiently uncorrelated (11). Alternatively, if two competing species have contrasting and asymmetric dispersal patterns, elevated levels of within-species competition can encourage the coexistence of the subordinate competitor (15). Finally, patchy dispersal behavior can increase the variety of coexisting species by decoupling the degree of spatial aggregation from the average dispersal distance (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that directionally biased movement of organisms can have significant effects on species coexistence (Levine, 2003;Lutscher, McCauley, & Lewis, 2007;Lutscher, Pachepsky, & Lewis, 2005;Salomon, Connolly, & Bode, 2010), metapopulation dynamics and stability (Elkin, Possingham, Michalakis, & DeAngelis, 2008;Wang, Haegeman, & Loreau, 2015), and metacommunity structure (Altermatt, Schreiber, & Holyoak, 2011;Bourgeois, GonzĂĄlez, Vanasse, Aubin, & Poulin, 2016;Dong et al, 2016). Mounting evidence now suggests that communities' dynamics can be indirectly coupled by the reciprocal spatial exchange of resources, even in the absence of dispersal of organisms (i.e., meta-ecosystem, Loreau, Mouquet, & Holt, 2003;Harvey, Gounand, Ganesanandamoorthy, & Altermatt, 2016).…”
Section: Introductionmentioning
confidence: 99%